Studies on Organic Acids and Minerals Content of Sourdough Naans Made from Different Extraction Rate Wheat Flours and Starter Cultures - Mueen-ud-Din, Ghulam; Salim-ur-Rehman; Anjum, Faqir Muhammad; Nawaz, Haq (Pakistan Journal of Nutrition, 2009)
Sourdough naans were prepared using different extraction rate wheat flours and sourdough starter cultures. Sourdough naans were analyzed to find out the effect of flour extraction rates on the production of organic acids and minerals content. It was concluded that organic acids (lactic, acetic and citric acid) increased with an increase in extraction rate and freeze dried cultures containing hetero-fermentative strains of LAB showed better performance than homo-fermentative in the production of organic acids. Similarly, minerals content were also increased with an increase in flour extraction and 100% extraction rate sourdough naan showed the highest minerals content.